Identification histological structure of femur and antebrachium Oryctolagus cuniculus as a biology learning - Aliffian Nisa’ Cholida; Sri Wahyuni (Green and Tropical Laboratory for Sustainability, 2024)
Background: Preparations are used as learning resources in histology practicum, for this reason, it is necessary to seek various ways to improve the quality, one of which is the manufacture of femoral and antebrachium preparations of Oryctolagus cuniculus. The rubbing preparations were obtained through the microtechnical method by boiling and rubbing the bones as thinly as possible. Objectives: The purpose of this study was to identify the histological structure of the femur and antebrachium tissue of Oryctolagus cuniculus which could be observed microscopically through bone rub preparations. Methods: This research method is descriptive. The research sample is taken from the femur and antebrachium Oryctolagus cuniculus. The data collection method was by direct observation of the preparations using a microscope and documented using an HP Realme camera directly from the microscope. The data analysis technique was carried out in a qualitative descriptive manner. The research was conducted at the Biology Laboratory of the University of Muhammadiyah Malang Results: Unstained femur and antebrachium preparations of Oryctolagus cuniculus show parts of the haversian system, namely Canalis havers, Osteocytes, Lacunae, Canaliculi, Lamella, and Canalis Volkmann. Conclusion: The research results can be used as learning resources or histology practicum media.